1992
DOI: 10.2500/105065892781976718
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind Study of the Effects of Loratadine versus Placebo on the Performance of Pilots

Abstract: The effects of a single 10-mg dose of loratadine on the performance of commercial and military pilots was compared with placebo in this randomized double-blind trial. Performance was evaluated by flight simulator tests carried out before and after pilots received active drug or placebo. Simulators were specificfor the DC-10, Boeing 747, and AT-26 Xavante fighter aircraft; all reproduced the respective conditions of flight. Pilots' performance, rated by observers blinded to the test, wasjudged to be within oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…23 Other studies also have shown that loratadine, 10 mg p.o., does not interfere with visuomotor coordination, digit symbol substitution, short-term memory, the ability to operate aircraft simulators, or performance in driving tasks. [35][36][37] Similarly, desloratadine is safe and nonsedating. 38 Psychomotor performance, BRT, and driving performance were not impaired by desloratadine.…”
Section: Sedative Potential and Changes In Cognitive Function With Nementioning
confidence: 99%
“…23 Other studies also have shown that loratadine, 10 mg p.o., does not interfere with visuomotor coordination, digit symbol substitution, short-term memory, the ability to operate aircraft simulators, or performance in driving tasks. [35][36][37] Similarly, desloratadine is safe and nonsedating. 38 Psychomotor performance, BRT, and driving performance were not impaired by desloratadine.…”
Section: Sedative Potential and Changes In Cognitive Function With Nementioning
confidence: 99%
“…The data obtained in these multiple-dose studies reflect 'real-life' conditions and are thus highly useful. application of learned strategy (Vuurman et al 1993), car tracking, simulated driving or flying tests Burns & Moskowitz 1980;Cohen et al 1985Cohen et al , 1987Gaillard et al 1988;Gengo et al 1990;Hindmarch & Bhatti 1987;Mattila et al 1992Mattila et al , 1993Moskowitz & Burns 1988;Neves-Pinto et al 1992;Offenloch & Zahner 1992;Rombaut et al 1991) or, where permitted, computer-monitored on-the-road driving tests (Aso & Sakai 1989;Betts et al 1984Betts et al , 1991O'Hanlon 1988b;Ramaekers et al 1992;Volkerts et al 1992) are believed to be more representative than simple tests of reaction time or memory. Performance tests for assessment of the effect of H I-antagonists on learned tasks involve sensorimotor coordination, memory, CNS arousal/information processing, and psychomotor tests (Adelsberg & D' Amico-Beadon 1990;Arriaga & Rombaut 1990;Bateman et al 1983;Bradley & Nicholson 1987;Bums & Moskowitz 1980;Chapman & Rawlins 1982;Clarke & Nicholson 1978;Cohen et al 1985Cohen et al , 1987De Roeck et al 1990;Dhorranintra et al 1986;Doms et al 1988;Gaillard et al 1988;Gengo et al 1987Gengo et al , 1990Goetz et al 1989Goetz et al , 199...…”
Section: The Blood-brain Barrier and Mechanisms Of Cns Adverse Effectsmentioning
confidence: 99%
“…Pseudoephedrine is shown to provide a local vasoconstriction to relieve symptoms of nasal stuffiness, while loratadine relieves rhinorrhea. In a double-blind trial of the effects of loratadine versus placebo in airline pilots, loratadine was shown to have no sedating effects that could affect pilots' performance (Neves-Pinto, Lima, & Teixeria, 1992). When compared with diphenhydramine, loratadine was superior in terms of worker productivity (i.e., an evaluation of task performance, not simply sedation) (Adelsberg 8c D'Amico-Beadon, 1990).…”
Section: Clinical Reviewmentioning
confidence: 99%